Impact of acetone on phase boundary of methane and carbon dioxide mixed hydrates - Partoon, B. (Elsevier, 2016)
In this work, the hydrate phase boundary of a gas mixture consisted of 29.9 mol CH4 and 70.1 mol CO2 is experimentally studied in the presence of 1-7 mol of an aqueous acetone solution. Results indicated that acetone acts as a weak inhibitor on this gas mixture. In addition, enthalpy of hydrate dissociation for this system is reported. Based on the results, the inhibition effect of acetone is found to be decreasing with the increase of acetone concentration while the enthalpy of hydrate dissociation is increasing with the increase of acetone concentration within the studied range. Â© 2015 Elsevier B.V.